Umerjanje objektiva "ribje oko" za fotografijo hemisfere - Diaci, Jurij (Zbornik gozdarstva in lesarstva, 2000)
Hemispherical photography represents one of the most appropriate methods of estimating averages of solar radiation over extended periods of time. This method is based upon the use of extremely wide-angle fisheye lenses, which produce large projection distortion. To correctly interpret hemispherical photography we have to know the projection characteristics of the fisheye lensin combination with a camera body. This can be achieved through lens calibration. The first part of the article explains in detail the calibration method for fisheye lenses which are used to assess the solar radiation in forest ecology research. In the second part the results of calibration for fisheye lens Sigma8 mm, f/4 (MF, N) are presented. The lens was used on a Nikon F50 camera body.
Keywords: fotografiranje; hemisfera; meritve; sončno sevanje